2011
DOI: 10.1002/ajpa.21484
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional kinematics of capuchin monkey bipedalism

Abstract: Capuchin monkeys are known to use bipedalism when transporting food items and tools. The bipedal gait of two capuchin monkeys in the laboratory was studied with three-dimensional kinematics. Capuchins progress bipedally with a bent-hip, bent-knee gait. The knee collapses into flexion during stance and the hip drops in height. The knee is also highly flexed during swing to allow the foot which is plantarflexed to clear the ground. The forefoot makes first contact at touchdown. Stride frequency is high, and stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 44 publications
5
50
1
2
Order By: Relevance
“…This standard description should not mask the diversity of bipedal modes that functional (biomechanical) investigations have demonstrated at the interspecific, intraspecific and ontogenetic levels [Kimura, 1985[Kimura, , 1991Franzen et al, 2003;Folia Primatol 2013;84:347-361 DOI: 10.1159/000353115 D' Août et al, 2004;Hirasaki et al, 2004;Vereecke et al, 2006;Berillon et al, 2010;Demes, 2011]. In the context of this study, we observed at least 2 submodes of bipedalism, with the trunk highly flexed to almost erect and variable flexion of the limbs.…”
Section: Infants Versus Adultsmentioning
confidence: 99%
“…This standard description should not mask the diversity of bipedal modes that functional (biomechanical) investigations have demonstrated at the interspecific, intraspecific and ontogenetic levels [Kimura, 1985[Kimura, , 1991Franzen et al, 2003;Folia Primatol 2013;84:347-361 DOI: 10.1159/000353115 D' Août et al, 2004;Hirasaki et al, 2004;Vereecke et al, 2006;Berillon et al, 2010;Demes, 2011]. In the context of this study, we observed at least 2 submodes of bipedalism, with the trunk highly flexed to almost erect and variable flexion of the limbs.…”
Section: Infants Versus Adultsmentioning
confidence: 99%
“…Because capuchins are quadrupedal but frequently walk upright [Fragaszy et al, 2004], they can serve as important models for studies on the evolution of human bipedalism [Demes, 2011]. Intermittent bipedalism requires high metabolic energy [Demes and O'Neill, 2013] particularly when associated with nut cracking and/or other activities [Liu et al, 2009] that represent complex behaviour in processing food [De Moraes et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Cebus/Sapajus demonstrates high cognitive and manipulatory behaviour [Antinucci and Visalberghi, 1986;Westergaard and Fragaszy, 1987;Garber, 1987;Costello and Fragaszy, 1988;Breseida and Ottoni, 2001;Tavares and Tomaz, 2002;Lima et al, 2003;Waga et al, 2006;Ottoni and Izar, 2008;Liu et al, 2009;De Moraes et al, 2014], as well as intermittent bipedalism [Demes, 2011]. Recent comparative anatomical analyses of bearded capuchins, baboons, chimpanzees and modern humans indicated…”
Section: Introductionmentioning
confidence: 99%
“…Bearded capuchins (Sapajus sp), unexpectedly, share with chimpanzees (Pan) various behavioral features such as high cognitive ability, good memory, tool use with intermittent bipedalism, and social tolerance (ANTINUCCI; VISALBERGHI, 1986;BOESCH;BOESCH, 1990;PHILLIPS, 1998;RYLANDS et al, 2000;TOMAZ, 2002;FRAGASZY et al, 2004;LOPES, 2004;VISALBERGHI et al, 2007;SABBATINI et al, 2008;DEFLER, 2009;MANNU;OTTONI, 2009;DEMES, 2011;DEMES;O´NEILL, 2012 however, their anatomical structures are like those of baboons (AVERSI-FERREIRA et al, 2005, 2010, 2011a, 2011b, 2013, 2014a, 2014b.…”
Section: Introductionmentioning
confidence: 99%